2014
DOI: 10.1038/srep07115
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and stable property of the cancer-associated heterotypic nucleosome containing CENP-A and H3.3

Abstract: The centromere-specific histone H3 variant, CENP-A, is overexpressed in particular aggressive cancer cells, where it can be mislocalized ectopically in the form of heterotypic nucleosomes containing H3.3. In the present study, we report the crystal structure of the heterotypic CENP-A/H3.3 particle and reveal its “hybrid structure”, in which the physical characteristics of CENP-A and H3.3 are conserved independently within the same particle. The CENP-A/H3.3 nucleosome forms an unexpectedly stable structure as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 40 publications
8
77
1
Order By: Relevance
“…CENP-A binds to HJURP during the G1 and G2 phases but not during the S phase (Bui et al, 2012). However, the current model of interconversion between tetrameric and octameric CENP-A nucleosomes in the cell cycle remains controversial (Fukagawa and Earnshaw, 2014; Hasson et al, 2013; Miell et al, 2013; Padeganeh et al, 2013), although the structures of the homotypic and heterotypic CENP-A particles have been solved (Arimura et al, 2014; Tachiwana et al, 2011). Therefore, we provide two models of epigenetic inheritance of CENP-A ubiquitylation: a tetramer model (Figure 7A) and an octamer model (Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CENP-A binds to HJURP during the G1 and G2 phases but not during the S phase (Bui et al, 2012). However, the current model of interconversion between tetrameric and octameric CENP-A nucleosomes in the cell cycle remains controversial (Fukagawa and Earnshaw, 2014; Hasson et al, 2013; Miell et al, 2013; Padeganeh et al, 2013), although the structures of the homotypic and heterotypic CENP-A particles have been solved (Arimura et al, 2014; Tachiwana et al, 2011). Therefore, we provide two models of epigenetic inheritance of CENP-A ubiquitylation: a tetramer model (Figure 7A) and an octamer model (Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…At these ectopic loci, CENP-A forms heterotypic nucleosomes (CENP-A/H3.3) occluding CTCF binding, and their presence may increase DNA damage tolerance in cancer cells (Lacoste et al, 2014). Arimura et al revealed a “hybrid” structure of the heterotypic CENP-A/H3.3 and suggested that the stable existence of the CENP-A/H3.3 nucleosome may cause ectopic kinetochore assembly (Arimura et al, 2014), which could lead to neocentromere formation and chromosome instability in cancer cells (Biermann et al, 2007; Lacoste et al, 2014; McGovern et al, 2012; Tomonaga et al, 2003; Wu et al, 2012). Our models of epigenetic inheritance of CENP-A ubiquitylation suggest that errors in CENP-A targeting, heterodimerization, and/or ubiquitylation induce abnormal accumulation of heterotypic nucleosomes (Figure 7B, bottom).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that CENP-A can form a heterotypic particle with H3.3 ). Furthermore, it had been shown recently that the heterotypic CENP-A/H3.3 nucleosome forms an unexpectedly stable structure as compared with the CENP-A nucleosome (Arimura et al 2014). Previously, we reported that incorporation of H3.3 can prevent the compaction of the chromatin fiber (Chen et al 2013); thus, we hypothesized that the dynamics of H3.3 at centromeres play important roles in the regulation of the higher-order organization of centromeric chromatin during the cell cycle.…”
Section: Cenp-a Chromatin Displays a Distinct Higher-order Organizationmentioning
confidence: 91%
“…Two recent crystallographic studies of CENP-A homotypic and CENP-A/H3.3 heterotypic nucleosomes revealed that, in comparison with H3.1 and H3.3, the αN helix of CENP-A is shorter, which results in a weaker interaction between DNA at the entry/exit site of CENP-A nucleosomes and histone cores and leads to an open conformation of the linker DNA (Luger et al 1997;Tachiwana et al 2011;Arimura et al 2014). In addition, a lysine in place of H3R49 in CENP-A probably results in a less protected αN helix of CENP-A, which consequently increases the flexibility of the linker DNA at the entry/exit sites of CENP-A nucleosomes (Conde e Silva et al 2007;Panchenko et al 2011).…”
Section: Cenp-a Chromatin Displays a Distinct Higher-order Organizationmentioning
confidence: 99%
“…During energy minimization of this constructed region, one residue in the n-terminus and c-terminus directions was unconstrained. Additionally, heterogen selenomethionine residues were altered to methionine through a single-atom mutation from Se to S. As a control, the 146 base-pair α-satellite DNA of PDB ID: 3WTP [61] was aligned onto 3AN2 using the CE algorithm [62] of PyMOL [63]. To further study the effect of acetylation on CENP-C binding, the CENP-C fragment [27] was docked onto each system using the CE algorithm [62] and simulated for an additional microsecond retaining identical simulation protocols.…”
Section: Methodsmentioning
confidence: 99%